A REVIEW ON SOLID LIPID NANOPARTICLES - RAJ, RIDHIMA; KOLAY, ARINDAM; HAVELIKAR, UJWAL (International Journal of Current Pharmaceutical Research, 2023)
Over the past decade, there has been a lot of research on solid lipid nanoparticles (SLNs), also known as lipid carriers. As a new lipid-based drug delivery technology for the topical applications of numerous medicinal drugs, solid lipid nanoparticles (SLNs) have demonstrated promise. SLNs have undergone considerable research on every continent and have become effective nano-sized medication carriers. There is no doubt that nano-formulations are extremely valuable tools for drug delivery applications; the current challenge is how to optimize them to ensure that they are safe, effective and scalable, so that they can be manufactured at an industrial level and advance to clinical use. In this context, lipid nanoparticles have gained ground, since they are generally regarded as non-toxic, biocompatible and easy-to-produce formulations. However, the processes governing SLN cellular uptake and absorption by topical application, as well as the mechanism of SLN drug release, are still unclear and need further research. To make SLNs easier to apply and to improve cutaneous and transdermal administration, it is also crucial to choose the right dose form and formulation base. Additional difficulties that could prevent the clinical translation of SLNs include scaling up and regulatory authorization. Therefore, the main focus of this research is on the various pathways that SLNs use to enter cells and penetrate skin. The physicochemical characteristics of SLNs are then thoroughly discussed, including numerous formulation and dosage form parameters that may affect SLN absorption via the skin. The translational status in relation to scale-up and regulatory issues are also covered in the discussion. Researchers interested in topical uses of SLNs for the effective delivery of medications and cosmetics will find this review to be helpful.